2017
DOI: 10.1016/j.cropro.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of viruses and viroids in ornamental citrus mother plants in Tuscany (Central Italy)

Abstract: Citrus tristeza closterovirus (CTV) has been found several times in the last decades in Italy, and plant protection services are involved in monitoring and surveillance. Although orchards linked to the citrus industry are well monitored, there is an underestimated risk of viruses or virus-like diseases in ornamental nurseries. Our aim was to modify a CTV monitoring program to include other viruses (Citrus variegation virus, CVV; Citrus psorosis virus, CPsV) and viroids (Citrus exocortis viroid, CEVd; Hop stunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In Italy, results of survey conducted in Campania region showed that CEVd was found to be the most widespread viroids infecting 68% of the tested samples [16]. Rizzo et al [17] found that CEVd was the most widespread viroid in ornamental nurseries in Tuscany (Central Italy), with an incidence reaching almost 50% in three years of monitoring. In Greece, CEVd was shown in high frequency as fourth most prevalent viroids where it was detected in 27.25% of samples collected from different geographical district of the country [18].…”
Section: Resultsmentioning
confidence: 99%
“…In Italy, results of survey conducted in Campania region showed that CEVd was found to be the most widespread viroids infecting 68% of the tested samples [16]. Rizzo et al [17] found that CEVd was the most widespread viroid in ornamental nurseries in Tuscany (Central Italy), with an incidence reaching almost 50% in three years of monitoring. In Greece, CEVd was shown in high frequency as fourth most prevalent viroids where it was detected in 27.25% of samples collected from different geographical district of the country [18].…”
Section: Resultsmentioning
confidence: 99%
“…Mother trees grown in pots or soil should be evaluated annually, and the samples should be sent to a certified laboratory for testing for CVC and HLB (CARVALHO et al, 2005). The occurrence of viruses and viroids in ornamental citrus mother trees was reported by Rizzo et al (2017) in Italy. The possibility of contamination with diseases transmitted by insect vectors from other plants and commercial orchards emphasizes the importance of the health care of citrus plants produced for all uses, not just in the production of nursery trees for use in industrial juice processing and the fresh fruit market.…”
Section: Production Of Propagation Materialsmentioning
confidence: 95%
“…This includes the availability of an adequate number of mother plants routinely controlled by the regional plant protection services by means of diagnostic molecular testing (i.e. PCR, RT-PCR, qPCR) for viruses and viroids (Rizzo et al, 2017). On the basis of the current legislation, any finding of quarantine pathogens in a nursery would involve the mandatory destruction of all the plants.…”
Section: Production Techniquesmentioning
confidence: 99%
“…On the basis of the current legislation, any finding of quarantine pathogens in a nursery would involve the mandatory destruction of all the plants. Currently, the Tristeza virus (CTV -Citrus Tristeza Virus) represents a major concern since its diffusion in commercial fruit production orchards in Sicily (Davino et al, 2003), whereas the most widespread viroid identified in Tuscan ornamental citrus tree nurseries was CEVd (Citrus exocortis viroid), frequently observed in C. × limonia and C. limon together with a high frequency of mixed viroid infections (Rizzo et al, 2017).…”
Section: Production Techniquesmentioning
confidence: 99%